2020
DOI: 10.1038/s41467-020-20057-8
|View full text |Cite
|
Sign up to set email alerts
|

Myonuclear content regulates cell size with similar scaling properties in mice and humans

Abstract: Muscle fibers are the largest cells in the body, and one of its few syncytia. Individual cell sizes are variable and adaptable, but what governs cell size has been unclear. We find that muscle fibers are DNA scarce compared to other cells, and that the nuclear number (N) adheres to the relationship N = aVb where V is the cytoplasmic volume. N invariably scales sublinearly to V (b < 1), making larger cells even more DNA scarce. N scales linearly to cell surface in adult humans, in adult and developing mice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 80 publications
1
62
0
1
Order By: Relevance
“…4) ). As we have suggested previously such flexibility might be related to either the number of nuclei limiting the maximum fiber size (Hansson, Eftestøl et al 2020), or the presence of some form of cooperativity between nuclei increasing their ability to produce volume (Cramer, Prasad et al 2020).…”
Section: Discussionmentioning
confidence: 84%
“…4) ). As we have suggested previously such flexibility might be related to either the number of nuclei limiting the maximum fiber size (Hansson, Eftestøl et al 2020), or the presence of some form of cooperativity between nuclei increasing their ability to produce volume (Cramer, Prasad et al 2020).…”
Section: Discussionmentioning
confidence: 84%
“…We propose that the impact of nuclear morphology and nuclear mechanotransduction in skeletal muscle homeostasis and adaptation is an area worthy of further investigation. To date, most of the work in skeletal muscle has focused on nuclear abundance as an important determinant of myofiber size and adaptation ( McCarthy et al, 2011 ; Murach et al, 2017 ; Psilander et al, 2019 ; Cramer et al, 2020 ; Hansson et al, 2020 ), with almost no focus on the nucleus as being a central player in the mechanotransduction response to mechanical load. The importance of nuclear mechanotransduction and the LINC complex in nuclear migration during myogenesis is well established ( Zhang et al, 2010 ; Gimpel et al, 2017 ; Stroud et al, 2017 ), yet whether this importance persists for tissue maintenance is unclear.…”
Section: Important Considerations and Future Directionsmentioning
confidence: 99%
“…However, interestingly, the reserve capacity is reduced in myofibers harboring 75% of myonuclei; thus, the myofiber size was similarly reduced to that of the myofibers with half the nuclei [ 68 ]. It has also been demonstrated that the number of myonuclei defines the size of myofibers in both humans and mice [ 69 ]. These studies also indicate the critical roles of myonuclear number and MuSCs, because MuSC is also responsible for the increase in myonuclear number during the developmental stage [ 70 ].…”
Section: Critical Roles Of Myonuclei Number For Size Of Myofibersmentioning
confidence: 99%